Associação em forrageio entre o Suiriri-cavaleiro (Machetornis rixosus, Tyrannidae) e a capivara (Hydrochoerus hydrochaeris, Rodentia) (Lundiana: International Journal of Biodiversity, 2013)
Several birds associate with grazing mammals to use them as perches, beaters or to feed on ectoparasites. Here, foraging strategies of the cattle-tyrant associated and non-associated to capybaras were compared. The study was developed in urban areas of Campinas, Brazil. Seventeen feeding bouts of cattle tyrants associated with capybaras and 16 of cattle tyrants in the absence of capybaras were timed. Feeding bouts of birds associated with capybaras were significantly longer than those of birds not associated with the mammals. This may be associated with the fact that association with capybaras enhance the birds efficiency in catching arthropods.